2006
DOI: 10.1073/pnas.0504789103
|View full text |Cite
|
Sign up to set email alerts
|

A dopamine transporter gene functional variant associated with cocaine abuse in a Brazilian sample

Abstract: The dopamine (DA) transporter DAT1 is a major target bound by cocaine in brain. We examined the influence of functional genetic variants in DAT1 on cocaine addiction. Repeat polymorphisms, including a 30-bp variable-number tandem repeat (VNTR) in intron 8 (Int8 VNTR) with two common alleles, were genotyped in cocaine-dependent abusers (n ‫؍‬ 699) and in controls with no past history of drug abuse (n ‫؍‬ 866) from Sã o Paulo, Brazil. Positive association was observed with allele 3 of the Int8 VNTR and cocaine a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
146
1
7

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 161 publications
(161 citation statements)
references
References 51 publications
(44 reference statements)
7
146
1
7
Order By: Relevance
“…27,28 An additional VNTR within intron 8 has recently been identified and is associated with both cocaine abuse and ADHD. 22,29 A preliminary study using a reporter gene construct found evidence that this VNTR is functional, with the 3-repeat allele showing reduced expression and heightened sensitivity to cocaine, relative to a 2-repeat allele. 29 Nevertheless, a regulatory role of the intron 8 VNTR in normally expressing DAT1 cells is yet to be established.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…27,28 An additional VNTR within intron 8 has recently been identified and is associated with both cocaine abuse and ADHD. 22,29 A preliminary study using a reporter gene construct found evidence that this VNTR is functional, with the 3-repeat allele showing reduced expression and heightened sensitivity to cocaine, relative to a 2-repeat allele. 29 Nevertheless, a regulatory role of the intron 8 VNTR in normally expressing DAT1 cells is yet to be established.…”
Section: Introductionmentioning
confidence: 99%
“…22,29 A preliminary study using a reporter gene construct found evidence that this VNTR is functional, with the 3-repeat allele showing reduced expression and heightened sensitivity to cocaine, relative to a 2-repeat allele. 29 Nevertheless, a regulatory role of the intron 8 VNTR in normally expressing DAT1 cells is yet to be established. Linking variation in the intron 8 marker to individual differences in cognition is an important next step in helping to establish the functional candidacy of this marker.…”
Section: Introductionmentioning
confidence: 99%
“…This polymorphism was studied in cocaine abuse and hyperactivity disorder (ADHD) patients showing a positive association with these disorders 19,24 . However, as far as we know, this is the fi rst association study analyzing this polymorphism in an OCD sample.…”
Section: Discussionmentioning
confidence: 99%
“…PCR products were separated on 2% agarose gels stained with ethidium bromide and viewed under UV light. The primers used were previously described in Guindalini et al 19 .…”
Section: Methodsmentioning
confidence: 99%
“…Our research group has conducted several major studies examining the genetic aspects of alcohol-and drugrelated disorders over the last few years [33][34][35][36][37][38][39]. This is an important area of research at our institute, and a project evaluating genetic vulnerabilities to cocaine addiction will be performed.…”
Section: Biological Aspects Of Alcohol-and Drug-related Disordersmentioning
confidence: 99%